Attitude to health and disease prevention of as a parameter of public health - O. V. Senatorova; V. A. Kuznetsov; A. S. Trufanov (Кардиоваскулярная терапия и профилактика, 2019)
The aim of this review was to summarize and analyze a number of population-based studies about attitudes to health and the prevention of cardiovascular diseases as a person’s life position. The article discusses the self-assessment of health as an independent predictor of morbidity in terms of gender and age, and also emphasizes that self-assessment of health is a multidimensional parameter of a person’s well-being. Attention is paid to the attitude of patients to treatment and medical activity, in particular cardiovascular diseases.